Emotional Cognitive Process as a Predominant Factor an Academic Performance - Stefania Guale Vásquez, Brenda; Elena Moya Martínez, María (International Journal of Psychosocial Rehabilitation, 2020)
The existence of man is characterized by his unique behavior and own, from birth to death is expressed through dialogue, gestures, movements, songs, sounds, and emotions. The emotions are of psychosocial study that to achieve a clear understanding one must know which and how many emotions a person experiences, the use, and management that they must have for better development in all the daily areas of life as it is in the educational field. Knowing about the emotions in the most changing stage and in the development of the human being was necessary to understand many of the positive and negative events that are experienced in the adolescence stage, there has been a confusion relating them to undisciplined students but in reality, it is that Teenagers express their emotions in different ways than any other being of another chronological age. The objective of the research was the analysis of the functionality of emotions in adolescent students that is in a range of age between 14-18 years as a predominant factor in academic performance. In the investigation of this work, the inductive-deductive and experimental methods were used where the behavior of the emotions of the adolescents in front of the school performance is evidenced. A literature review was conducted to contextualize the research; In addition to qualitative and quantitative analysis to make an interpretation of the instrument applied. In this research, we will find the main information about emotions, their conceptualization and their functionality in adolescents about the application in the educational field and the relationship between the terms of this research. At the end of this investigation, the analysis of the results of the applied survey and the cited bibliography are exposed, this will serve as fundamental support in the realization of this research work.